2016
DOI: 10.1039/c6mb00181e
|View full text |Cite
|
Sign up to set email alerts
|

Association between the metabolome and bone mineral density in pre- and post-menopausal Chinese women using GC-MS

Abstract: The present study describes for the first time, a metabolic profile reflecting the osteoporosis progression in 364 pre- and postmenopausal Chinese women using GC-MS. In order to accurately evaluate the dynamic changes of metabolites along with estrogen deficiency and osteoporosis progression, we divided these subjects into the following four groups: premenopausal women with normal bone mass density (BMD, group I), postmenopausal women with normal BMD (group II), postmenopausal women with osteopenia (group III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
(31 reference statements)
7
46
0
1
Order By: Relevance
“…Although the total TG amounts were not changed in HDL in our study, they were significantly increased in the LDL fraction due to contributions from two highly unsaturated TG species (50:4 and 54:6). While the relationship between the increase of TG and the development of PMOp is not clearly understood, similarly to our study, the overall TG level has been reported to increase in postmenopausal women [35]. Moreover, TG species with more unsaturated acyl chains appear to be more influenced than those with saturated chains.…”
Section: Lipid Alterations In Each Lipoprotein From Patients With Pmopsupporting
confidence: 77%
“…Although the total TG amounts were not changed in HDL in our study, they were significantly increased in the LDL fraction due to contributions from two highly unsaturated TG species (50:4 and 54:6). While the relationship between the increase of TG and the development of PMOp is not clearly understood, similarly to our study, the overall TG level has been reported to increase in postmenopausal women [35]. Moreover, TG species with more unsaturated acyl chains appear to be more influenced than those with saturated chains.…”
Section: Lipid Alterations In Each Lipoprotein From Patients With Pmopsupporting
confidence: 77%
“…Through the comparison of metabolic differences among different groups, researchers are able to identify specific and sensitive metabolites that would be used in the diagnosis and prognosis of osteoporosis. A study from Qi et al involved 364 female subjects divided into four groups (premenopausal women with normal BMD, postmenopausal women with normal BMD, postmenopausal women with osteopenia and postmenopausal women with osteoporosis), from Jiangsu Province geriatric hospital, China [22]. They studied the connection between osteoporosis progression and BMD in postmenopausal women and discovered biomarkers that could distinguish low BMD from normal BMD.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Patients with lower BMD and osteoporosis also have higher lipid levels. Qi et al found that postmenopausal women with osteopenia and osteoporosis had lower concentration of high-density lipoprotein cholesterol (HDL-C) and higher concentrations of low-density lipoprotein cholesterol (LDL-C), triglycerides and total cholesterol [22]. The result from Xue et al showed that ovariectomy induced an increase of plasma levels of low-density lipoprotein (LDL), choline, glycerophosphatide and lipid in mice, which indicated that the biological mechanism of osteoporosis is associated with lipid metabolism [51].…”
Section: Biological and Metabolic Significance Of The Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations